In search for rules that secure gains from cooperation: The heuristic value of social dilemmas for normative institutional economics - Martin Petrick; Ingo Pies (Martin-Luther-Universität Halle-Wittenberg, Lehrstuhl für Wirtschaftsethik, 2005)
We ask how normative statements are possible within an economic theory framework that recognises the importance of institutional arrangements. Instead of applying established outcome-oriented criteria of social welfare, we examine whether the rules of economic interaction allow the acquisition of gains from cooperation. We suggest to reconstruct any interaction as an existing or repealed social dilemma. This approach helps to identify common rule interests which create room for improvement of all parties involved, and to suggest desirable institutional reforms. Our policy applications include credit markets in developing countries and the unemployment problem in Europe.
urn:nbn:de:gbv:3:2-2753
Keywords: D02; D63; D74; 330